Science Teaching-Learning in Online Mode: A Study of Techno-pedagogical Knowledge Development in Teachers - Akalamkam, Kalyani (SCHOOL SCIENCE, 2021)
Digital Technologies (DTs) are a widely recognised aspect of 21st century skills for teachers. The unprecedented COVID-19 pandemic has forced schools to suddenly close down and shift to complete online teaching. This paper explores the practicalities and reflection of teachers in terms of their confidence in teaching science using various digital technologies during online classes using TPACK framework. The sample constitutes of 81 government and private school science teachers of Delhi NCR (India) and the study used mixed methods approach. The study focused on the four technological dimensions of TPACK i.e., TK, TCK, TPK. It was found that most of the teachers had taken selfinitiative to learn and adapt to sudden shift to complete online teaching. Though initially teachers found it daunting and challenging to adapt to completely technology-based teaching, they gradually gained confidence in using various digital platforms in teaching of science. Analysis of the data revealed that increase in teachers’ confidence levels was most in TPK and least in TCK. There is positive and moderately high correlation between all domains of TPACK. The findings of this study have implications for professional development programmes which can focus on use of various DTs to support inquiry in science classroom than mere sharing of information